Penyesuaian Hasil Dapatan Kajian Pelanggan Muzium & Galeri Tuanku Fauziah, USM dengan Strategi Kuratorial Pameran e-CITRA: Adaptation of Audience-Research Findings at the Muzium & Galeri Tuanku Fauziah (MGTF) with e-CITRA Curatorial Strategies - Hasnul J Saidon, Nor Laila Abd Rozak@Razak dan Safinawati Samsudin (Wacana Seni Journal of Arts Discourse, 2011)
The discussion on contemporary visual art exhibition is often focused on artworks, creation and visual artists. Theoretical framework of such discussion is normally constrained by formalistic and aesthetic reading methodologies. In this article, the discussion of an exhibition called e-CITRA is done through the framework of an audience research, its findings and application of the findings in curatorial strategies. By using e-CITRA and the compatibility of its hybrid concept with the curatorial model of Muzium & Galeri Tuanku Fauziah (MGTF) as a case example and theoretical basic, the article explicates on how the quantitative findings from an audience research can be used to establish curatorial strategies for e-CITRA.As a result, the exhibition compliments the profile of MGTF's audience, thus creating a more inclusive, sustainable and expansive visiting experience.